Harmoni Batin : Terapi Dzikir Dalam Meningkatkan Harga Diri Lansia di Panti Sosial Trisna Werda Budi Mulia II Cengkareng - Tri Setyaningsih; Ribka Sabarina Panjaitan; Yurita Mailintina; Dian Fitria; Lipin Lipin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Inner Harmony: Dhikr Therapy in Increasing the Self-Esteem of the Elderly in the Trisna Werdha Budi Mulia II Cengkareng Social Institution is a therapeutic approach that focuses on increasing the self-esteem of the elderly living in the social institution. This therapy, which integrates dhikr (a form of Islamic meditation), aims to promote inner harmony and spiritual growth among the elderly. By increasing self-confidence and self-esteem, this therapy can improve the welfare and quality of life of elderly people in social institutions. From 30 respondents, the N-Gain Score was 58.0. This shows that the method used by researchers in this activity is quite effective. Apart from that, the N-Gain Score obtained at 0.58 places the category or strength in this community service activity at a relatively moderate level. In other words, even though the method used is effective, there is still room for improvement so that the results achieved can be maximized. This N-Gain Score value indicates that there is a significant increase, but not in a very high category, indicating quite good effectiveness but needs further development to achieve optimal results.